2013
DOI: 10.3892/etm.2013.1304
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of systemic lupus erythematosus and rheumatoid arthritis with complements C3 and C4 and C-reactive protein

Abstract: The aim of this study was to analyze the changes in complements C3 and C4 and C-reactive protein (CRP) in patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA), and to evaluate the role of these indices in the differential diagnosis of SLE and RA. The first 347 patients with SLE, 382 patients with RA and 66 patients with erythema nodosum were selected for the measurement of complement and CRP levels in the serum, the erythema nodosum patients were the control group. The roles of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…11 At the same time, the complement levels were found to increase in inflammatory pathologies. 12 That's why decreased MPV, C3 and C4; increased CRP, ASO, C3, and C4 were evaluated as risk factors. The clinical and laboratory findings predicting the organ or system involvement were tried to be determined.…”
Section: Methodsmentioning
confidence: 99%
“…11 At the same time, the complement levels were found to increase in inflammatory pathologies. 12 That's why decreased MPV, C3 and C4; increased CRP, ASO, C3, and C4 were evaluated as risk factors. The clinical and laboratory findings predicting the organ or system involvement were tried to be determined.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to C4, there is still some uncertainty about the use of this parameter as biomarker for the diagnosis of lupus activity. One study reported that serum levels of C4 are useful in disease activity evaluation in patients with SLE [ 59 ]. In contrast, another study found that serum levels of C4 split product C4d rather than C4 can be used as biomarker for lupus activity [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mosca et al [ 32 ] suggested that an elevated C4 level could be associated with intermittent atopic asthma. Meanwhile, many studies have identified that C4 might be a biomarker for forecasting systemic lupus erythematosus [ 33 34 ]. Therefore, C4 might be related to acute inflammation and the immune response.…”
Section: Discussionmentioning
confidence: 99%